2016
DOI: 10.1590/1678-98652016000400006
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da suplementação com ácidos graxos ômega-3 nas subfrações da lipoproteína de alta densidade de indivíduos tabagistas

Abstract: ObjetivoAvaliar o efeito da suplementação com ômega-3 nas subfrações das lipoproteínas de alta densidade em indivíduos tabagistas. MétodosEnsaio clínico, randomizado, duplo-cego. Foi selecionada uma amostra com 33 tabagistas, de ambos os sexos, com idade entre 30 e 60 anos, suplementados com ômega-3 (n=17) ou placebo (ácidos graxos ômega-6, n=16) por dois meses. As subfrações das lipoproteínas de alta densidade foram analisadas pelo sistema Lipoprint. Os testes estatísticos foram realizados com o auxílio do pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A clinical, randomized, double-blind trial performed with 33 smokers showed that nutritional therapy with supplementation of omega-3 during 8 weeks (1 capsule 3x/day) was able to positively change the fractions of high-density lipoproteins. Changing the rates of cholesterol, providing increased high-density lipoproteincholesterol (HDL) and reduction of low-density lipoproteincholesterol (LDL), resulting in a reduction in the occurrence of cardiovascular complications 15 .…”
mentioning
confidence: 99%
“…A clinical, randomized, double-blind trial performed with 33 smokers showed that nutritional therapy with supplementation of omega-3 during 8 weeks (1 capsule 3x/day) was able to positively change the fractions of high-density lipoproteins. Changing the rates of cholesterol, providing increased high-density lipoproteincholesterol (HDL) and reduction of low-density lipoproteincholesterol (LDL), resulting in a reduction in the occurrence of cardiovascular complications 15 .…”
mentioning
confidence: 99%